Attributes of an Effective Clinical Teacher in Undergraduate Medical Education: Students' Perspective - Noor-; Haris Iqbal; Wajid Butt (Aziz Fatimah Medical and Dental College, 2019)
Background: A good clinical teacher constitutes one of the major factors towards providing quality educational environment in the wards for medical students. Modern era has opened new domains for defining methods for clinical teaching as well as new roles for a clinical teacher. This study aims at exploring medical student' perspectives regarding attributes of an effective clinical teacher. Methods: This mixed method study involved final year MBBS students of Aziz Fatima Medical and Dental College, Faisalabad from August 2018 to November 2018.Seventy-five medical students filled the Nursing Clinical Teacher Effectiveness Inventory (NCTEI) questionnaire after taking informed consent. This was followed by seven individual face to face interviews of students consenting for interview. Results: Most important attribute for an effective clinical teacher was reported having good interpersonal skills (95.2%) followed by having skills of evaluation (90.7%) , clinical competence (84.7%) , good personality traits (83.2%) and teaching skills (81.1%).Students felt it most important to have a teacher who is approachable and with whom they can communicate easily. Conclusion: In the present era of medical education, an undergraduate medical student expects his clinical teacher to be approachable, professional, a positive role model with good interpersonal and teaching skills